PERENCANAAN PEMBERDAYAAN MASYARAKAT MELALUI PEMBENTUKAN RELAWAN PEMADAM KEBAKARAN DI KABUPATEN SUBANG: SEBUAH TINJAUAN - Sutangsa Sutangsa; Endang Suryana (LPPM Institut Pendidikan Nusantara Global, 2023)
The progress of development in the Subang Regency area demands the readiness of the local government to further improve services in various aspects/sectors including health, education, economy, as well as improving security services, community welfare, and community protection including fire affairs in accordance with existing laws and regulations. apply. With the condition of a fairly large area, the amount of infrastructure owned and the existing human resources, the responsibility for preventing and overcoming fire hazards is the responsibility of all of us, in this case the government, the community and themselves. For this reason, community empowerment through the formation of volunteer firefighters is needed in order to create self-reliance and help firefighters achieve a level of response time. The theory used in this research is planning theory and community empowerment theory. The meaning contained in planning is the basis for achieving the goals of better and orderly social change. While the theory of community empowerment explains the existence of power and the ability to give to other parties. This theory reveals that people involved in the empowerment process must have the awareness to participate actively and have the ability to increase their capacity. This research was conducted using qualitative research methods. The use of this method is intended to understand in depth the phenomenon of the community empowerment program planning process through the Formation of Volunteer Firefighters. The location of this research is the Civil Service Police Unit and the Subang Regency Fire Department. The focus of this research lies in the stages of the planning process for the empowerment program which makes the subject groups of government-assisted empowerment.